2023
DOI: 10.1108/scm-12-2022-0484
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging on technology and sustainability to innovate the supply chain: a proposal of agri-food value chain model

Abstract: Purpose Nowadays, the agri-food industry is called to face several sustainability challenges that require the development of new sustainable models. The adoption of new technological assets from Industry 4.0 supports the companies during the implementation of sustainability practices. Several models design the operation management of the food supply chains (FSCs). Because none extant models resulted complete in technological and sustainability elements, this paper aims to propose an innovative and sustainable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Past research signifies the role of digitalisation in overcoming sustainability challenges in agri-food value chains (Corallo et al. , 2023).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Past research signifies the role of digitalisation in overcoming sustainability challenges in agri-food value chains (Corallo et al. , 2023).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Some actors view system building as creating new value streams from waste while others see it as harnessing new value from alternative supply chains (Bocken et al, 2014). Recent research reviewed 15 food supply chain models and identified similar gaps in literature with regard to some value streams not being captured within the core business model by the key actors in agri-food supply chains (Corallo et al, 2023). These value streams (e.g.…”
Section: Sustainable Business Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…With the growing applications of Industry 4.0 technologies and their capabilities, digital transformation has captured the attention of researchers in the field of supply chain management. The transformation prompted by emerging technologies targets existing challenges and creates a positive impact on supply chain performance (Swierczek, 2023;Lerman et al, 2022) through improved product quality, productivity, efficiency and sustainability (Corallo et al, 2023;Bourlakis and Paul, 2008).…”
Section: Digital Transformation With Internet Of Things Cloud Computi...mentioning
confidence: 99%
“…Food fraud poses a significant economic and potential food safety problem for industry, consumers, and governments worldwide (Visciano & Schirone, 2021). The agri-food industry operates on a global scale, encompassing multiple stakeholders such as farmers, processors, distributors, and retailers (Corallo et al, 2023). Within this complex system, these stakeholders are confronted with diverse challenges that include ensuring food traceability, upholding food safety standards, and fostering transparency throughout the supply chain (Friedman & Ormiston, 2022).…”
Section: Introductionmentioning
confidence: 99%